PENERAPAN MODEL CHILDRENT LEARNING IN SCIENCE (CLIS) BERBANTUAN CANVA UNTUK MENINGKATKAN KEMAMPUAN KOLABORASI SISWA KELAS V SD - Kartini, Intan Ega Tantris; Rita Nurharyani, Galih Dani Septiyan Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
his study is about the Canva-assisted Children Learning In Science (CLIS) model in improving collaboration skills among fifth grade students. This study was motivated by the need to integrate innovative pedagogical strategies that not only improve the understanding of scientific concepts but also foster collaboration skills needed in 21st century learning. This study used a quantitative descriptive method with a pre-experimental design involving a pretest and post-test structure, involving 30 students in fifth grade. Data collection techniques were carried out through the test and observation process during the learning process. The findings show that the use of the Canva-assisted CLIS model significantly improves students' collaboration skills. The data obtained will be analyzed using SPSS software to see cognitive changes and the development of students' collaboration skills. Analysis of the quantitative data results revealed that students showed significant progress in collaboration, as reflected in group activities and student project results. These results underscore the importance of integrating digital tools in educational environments to enhance collaborative learning, indicating that the Canva-assisted CLIS framework serves as an effective means to prepare students for collaborative challenges in learning environments.